2019
DOI: 10.1108/cdi-12-2018-0312
|View full text |Cite
|
Sign up to set email alerts
|

Career adaptability and citizenship outcomes: a moderated mediation model

Abstract: Purpose Drawing upon the career construction theory (Savickas, 2002, 2013) and the conservation of resources theory (Hobfoll, 1989, 2001), the purpose of this paper is to explore whether, how and when career adaptability influences citizenship outcomes (i.e. citizenship behavior and citizenship fatigue). Design/methodology/approach Two-wave data were collected from 306 employees working in the operation department of an e-commerce company in Eastern China. Findings The results showed that both affective co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…A few studies explored boundary conditions, mainly focussing on environmental factors. For example, Liu and Yu (2019) found that career adaptability had a stronger influence on citizenship behaviour when there were more hindrance stressors. Federici et al (2021) found that when organizations took more high-performance work practices, career adaptability improved work engagement more significantly.…”
Section: Career Adaptability and Work-related Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies explored boundary conditions, mainly focussing on environmental factors. For example, Liu and Yu (2019) found that career adaptability had a stronger influence on citizenship behaviour when there were more hindrance stressors. Federici et al (2021) found that when organizations took more high-performance work practices, career adaptability improved work engagement more significantly.…”
Section: Career Adaptability and Work-related Outcomesmentioning
confidence: 99%
“…Recently, some scholars began to examine whether career adaptability could help people perform better at work. They found that career adaptability makes people perform in‐role tasks more effectively (Ohme & Zacher, 2015), show more helping behaviour (Lan & Chen, 2020; Liu & Yu, 2019), display less counterproductive behaviour (Yu et al, 2019), obtain higher satisfaction with their jobs (Fiori et al, 2015) and develop lower intention to leave (Zhu et al, 2019), arguably because it helps people adapt to work demands, job requirements and normative expectations.…”
Section: Introductionmentioning
confidence: 99%
“…From a practical perspective, these results suggest that individuals should be proactive in acquiring career resources (adaptabilities) and focus more on job engagement as strategies to manage career development. Given that career adaptabilities are malleable competencies (Savickas and Porfeli, 2012), and the acquisition of these competencies is more likely to result in engagement and higher task performance, organizations and career counselors should consider implementing career development training programs that encourage employees (regardless of their personal disposition) to advance their career adaptability resources (Liu and You, 2019; van der Horst and Klehe, 2019). These programs will likely help individuals, especially those less inclined to take initiative, acquire the necessary proactive aptitudes to effectively develop career adaptability and attain their work goals.…”
Section: Discussionmentioning
confidence: 99%
“…Geboers et al (2014) link active participation in social action with committed citizenship, thus, indicating that career guidance in groups has potential to develop active citizenship; a goal of many universities today. Liu & Yu (2019) showed that career adaptability leads to better citizenship outcomes and that this relationship is mediated by the ability to accept organisational values and goals (affective commitment) and the psychological resourcefulness to the stress experienced in working life (emotional exhaustion). This is particularly relevant in a post pandemic environment where stressors may be higher and increase emotional exhaustion, reducing career adaptability.…”
Section: Literature Reviewmentioning
confidence: 99%